Isobutane dehydrogenation by oxidizing in isobutene on Ni-V-Sb/γAl2O3 catalytic system - V. P. Vislovsky; R. M. Talyshinsky; V. F. Tretyakov; N. A. Frantsuzova; V. E. Shejnin (Тонкие химические технологии, 2009)
Addition of nickel oxide in the V-Sb/γAl2O3 catalytic system, used in oxidative dehydrogenation of isobutane, significantly increases conversion (from 36 to 42-44%) at isobutene selectivity of 70 %. The developed catalysts consisting of systems V-Sb-O and V-Sb-Ni-O were characterized using XRD, XPS, and H2-TPR. Formation of the discovered nickel vanadate phase NiV2O6 is as a result of free phase VOx is a more effective catalyst due to increase in the quantity of mobile oxygen lattice. It is suggested that the set of various vanadium surface phases improves activity and selectivity of the new catalytic systems.